Effect of Streptococcus uberis on Gamma Delta T Cell Phenotype in Bovine Mammary Gland - Slama, Petr; Zavadilova, Terezie; Pavlik, Ales; Horky, Pavel; Skalickova, Sylvie; Skladanka, Jiri; Roychoudhury, Shubhadeep; Baldovska, Simona; Kolesarova, Adriana; Konecny, Roman; Tancin, Vladimir; Zouharova, Monika (Animals, 2021)
In this study, we focused analyzing γδ T cells during bovine mammary gland inflammation induced by Streptococcus uberis. A mammary gland cell suspension was obtained using lavage 24, 48, 72, and 168 h after intramammary-induced infection. The proportion of lymphocytes increased during the entire week in which inflammation was present. The γδ T cells were also elevated during inflammation, reaching their peak at 72 h following induced inflammation. The percentage of apoptotic lymphocytes continually increased, with the highest proportion occurring 168 h after S. uberis infection. The results show that γδ T cells may be involved in the resolution of inflammation in bovine mammary glands, with the apoptosis of those cells potentially playing an important role.
Keywords: T cell; lymphocyte; Streptococcus uberis; mastitis; apoptosis; mammary gland